Plant Microbiomes Alleviate Abiotic Stress-Associated Damage in Crops and Enhance Climate-Resilient Agriculture - Fazal Ullah; Sajid Ali; Muhammad Siraj; Muhammad Saeed Akhtar; Wajid Zaman (Plants)
Plant microbiomes, composed of a diverse array of microorganisms such as bacteria, fungi, archaea, and microalgae, are critical to plant health and resilience, playing key roles in nutrient cycling, stress mitigation, and disease resistance. Climate change is expected to intensify various abiotic stressors, such as drought, salinity, temperature extremes, nutrient deficiencies, and heavy metal toxicity. Plant-associated microbiomes have emerged as a promising natural solution to help mitigate these stresses and enhance agricultural resilience. However, translating laboratory findings into real-world agricultural benefits remains a significant challenge due to the complexity of plant–microbe interactions under field conditions. We explore the roles of plant microbiomes in combating abiotic stress and discuss advances in microbiome engineering strategies, including synthetic biology, microbial consortia design, metagenomics, and CRISPR-Cas, with a focus on enhancing their practical application in agriculture. Integrating microbiome-based solutions into climate-smart agricultural practices may contribute to long-term sustainability. Finally, we underscore the importance of interdisciplinary collaboration in overcoming existing challenges. Microbiome-based solutions hold promise for improving global food security and promoting sustainable agricultural practices in the face of climate change.